PERBAIKAN METODE KERJA UNTUK MENINGKATKAN PRODUKTIVITAS PADA PROSES PENGUPASAN BAWANG PUTIH (STUDI KASUS: UKM ULAK KARANG PADANG) - Huda, Ashila Nurul (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
Garlic is one of the most useful and popular types of onions in Indonesia. It has many benefits in daily life. In Indonesia, especially in West Sumatra, garlic is most commonly used as a cooking spice in traditional restaurants. Restaurants in West Sumatra typically require peeled garlic since they lack the time to peel large quantities for cooking. This situation creates an opportunity for household industries to supply peeled garlic in large amounts. One of the household industries producing peeled garlic in West Sumatra, particularly in Padang, is Usaha Kelas Menengah (UKM) Ulak Karang. This business carries out the garlic peeling process using two methods: manual peeling and machine-assisted peeling. Based on observations using a man and machine process chart, the main issue faced by UKM Ulak Karang is setup time. The machine is utilized only 15% of the time, while idle time reaches 85%. Workers spend 76% of their time on setup, 15% on idle time, and 9% on allowances. The setup time in the garlic peeling process significantly affects daily production output. Reducing setup time can accelerate the process, allowing production targets to be met. Additionally, increasing the daily volume of peeled garlic leads to higher income for UKM Ulak Karang. To address this issue, the Single Minute Exchange of Die (SMED) method was applied directly to workers at UKM Ulak Karang. As a result, setup time was reduced by 58.29%, and production output increased by 71.55%